Urinary DcR2/Cr level predicts renal outcomes in patients with diabetic kidney disease - Jia Chen; Weidong Wang; Fang Yu; Xiaoyue Wang; Yani He; Kehong Chen (Journal of Clinical & Translational Endocrinology)
In diabetic kidney disease (DKD), urinary decoy receptor 2 (uDcR2) levels are associated with tubulointerstitial fibrosis; however, whether uDcR2 can predict renal outcomes remains unclear. Herein, we analyzed the association between uDcR2 and renal outcomes (defined as a composite of a serum creatinine (SCr) increase of 50 % from baseline, or initiation of dialysis for end-stage renal disease) in 153 patients with biopsy-proven DKD. Patients were divided into the composite (n = 67) and no composite (n = 86) outcome groups. uDcR2 levels were measured using ELISA. The area under the receiver operating characteristic curve (AUC) for uDcR2 in discriminating DKD renal outcomes was calculated. Kaplan–Meier survival analysis and multifactorial Cox regression models evaluated the association between uDcR2 levels and renal outcomes. Renal DcR2 mRNA and protein expression were detected using in situ hybridization and immunohistochemical staining. Immunofluorescence revealed DcR2 and α-SMA colocalization. uDcR2/Cr levels were higher in patients in the composite than the no composite outcome group. uDcR2/Cr levels positively correlated with ACR, SCr, interstitial fibrosis and tubular atrophy (IFTA), and negatively correlated with eGFR. uDcR2/Cr had an AUC of 0.825 at the optimal cut-off value of 389 ng/gCr. Addition of uDcR2/Cr to ACR, eGFR, or IFTA improved renal outcome predictions. Renal survival was significantly lower at uDcR2/Cr ≥ 389 ng/gCr. Patients in the composite group had higher tubular DcR2 mRNA and protein level percentages. α-SMA was significantly increased in DcR2-positive renal tubules and their surroundings. Overall, uDcR2/Cr is an independent predictor of renal outcomes, with potential for improving the prevention and treatment of DKD.